PENGARUH KOMUNIKASI INTERPERSONAL KELUARGA DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMKN 1 SOLOK SELATAN. - REMON, REMON; Hia, S.Pd MM, Yulna Dewita; Areva, S.Pd, Desi (Pendidikan Ekonomi, 2014)
ABSTACTThe impact of this research is to find out the interpersonal communication and economic interests of the studentsâ study at X SMKN 1 south solok. Technique of analysis data used by the linear regression analyses was of significant 44.70 with a double standard.The result showed that interpersonal communication: (1) the first grade student of SMKN 1 south solok Â is good. With average score 3.78 percent, and TCR 75,62. To interest the students of SMKN 1 south Solok is good whether it can be seen from the average score of 3, 74 and TCR 74,88 %. (2) the interpersonal communications variable influence significantly to study the student with a sig smaller than alpha 0,00 0.05 and variable interest to learn significant results are influence students with a sig smaller than alpha 0,00 < 0.05 (3) the coofisiensi determination Â is 0,712 that interpersonal communications the learning of the learned and the interests of the remaining 71,2 % by 28.8 % influence by these factors. As a result, its giving the maening for the influence that has significant communication international variable family and studentsâ attantion for a result of their economy study at SMKN 1 south Solok.Advised for the students to establish a better communication between a parent (mother father) and the son and also to increase their interest in learning and interest for the good and the study will be increased. Then for parents Â hope to take a little time to communicate to ask about students Â students learning activity. So, its can grow the studentsâ interest in studying, for teachers, to motivate and consider the students are interested in learning of the learned and students are getting better.